Needs and Requirements of Modern Biobanks on the Example of Dystonia Syndromes - Lohmann, Ebba; Gasser, Thomas; Grundmann, Kathrin (Frontiers in Neurology, 2017)
Dystonia belongs to a group of rare diseases characterized by etiologic heterogeneity, affection often in childhood, severe and variable clinical manifestation. The burden of this disease is aggravated by the lack of effective and specific treatment. In the field of dystonia as in other rare diseases the number of available biospecimens is, in general, limited. Here we report a new approach to collect clinical and genetic data in biospecimens maintained collaboratively by researchers and their associated institutions in a decentralized system. Allowing researchers to have access to significant numbers of samples and corresponding clinical data, biobanking in dystonia might provide a powerful tool in the identification of disease genes but also the classification of variants detected in known genes with respect to their clinical relevance. Growing data in genetics due to the technical progress demand for well annotated and well managed biobanks, which in near future hold even the potential for biomarker research and generating medical treatment based on clinical and genetic currently summarized as “personalized medicine”.